A universal cell‐free DNA approach for response prediction to preoperative chemoradiation in rectal cancer. Issue 7 (14th December 2022) - Grinshpun, Albert; Kustanovich, Anatoli; Neiman, Daniel; Lehmann‐Werman, Roni; Zick, Aviad; Meir, Karen; Vainer, Elez; Granit, Roy Z.; Arad, Amit; Daskal, Noa; Schwartz, Ruth; Sapir, Eli; et al.
Abstract: The standard treatment approach for stage II/III rectal cancer is neoadjuvant chemoradiation therapy (nCRT) followed by surgery. In recent years, new treatment approaches have led to higher rates of complete tumor eradication combined with organ‐preservation strategies. However, better tools are still needed to personalize therapy for the individual patient. In this prospective observational study, we analyzed colon‐derived cell‐free (cf)DNA (c‐cfDNA) using a tissue‐specific DNA methylation signature, and its association with therapy outcomes. Analyzing plasma samples (n = 303) collected during nCRT from 37 patients with locally advanced rectal cancer (LARC), we identified colon‐specific methylation markers that discriminated healthy individuals from patients with untreated LARC (area under the curve, 0.81; 95% confidence interval, 0.70‐0.92; P  < .0001). Baseline c‐cfDNA predicted tumor response, with increased levels linked to larger residual cancer. c‐cfDNA measured after the first week of therapy identified patients with maximal response and complete cancer eradication, who had significantly lower c‐cfDNA compared with those who had residual disease (8.6 vs 57.7 average copies/ml, respectively; P  = .013). Increased c‐cfDNA after 1 week of therapy was also associated with disease recurrence. Methylation‐based liquid biopsy can predict nCRT outcomes and facilitate patient selection for escalation and de‐escalation strategies. Abstract : What's new? The treatment of locally advanced rectal cancer is a rapidly evolving field, involves multidisciplinary decision‐making, and has no predictive biomarkers for optimal treatment selection. Here, we show that cell‐free DNA from colorectal cells can be identified in patients with rectal cancer, using tissue‐specific methylation markers. Furthermore, cell‐free DNA levels and dynamics are correlated with individuals' outcomes in patients undergoing neoadjuvant chemoradiation for locally advanced rectal cancer.